BENTUK PARTISIPASI MASYARAKAT DALAM UPAYA PEMBERDAYAAN MELALUI KEGIATAN PENGEMBANGAN USAHA COCOPOT DI DESA LAMBANGI KECAMATAN KOLONO TIMUR KABUPATEN KONAWE SELATAN - Jayadisastra, Yoenita; Lasinta, Megafirmawanti (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
The purpose of this study was to determine how the form and level of participation in Cocopot business development empowerment activities in Lambangi Village, East Kolono District, South Konawe Regency. Participation is part of community involvement to succeed development programs. Cocopot business conducted in the village of Lambang proved to help the welfare of the community, most of whose business actors are the people of the area. This study uses quantitative descriptive methods in the hope of being able to state the facts that occur in the field. The sample in this study amounted to 26 people consisting of 4 groups of coastal women in Lambangi Village. The results showed that the form of participation in cocopot development in Lambangi village was dominated by the participation of personnel, followed by the participation of skills, thoughts, property and social. At the level of community participation in Lambangi Village is at the level of degrees of Tokenism, namely participation that only accepts decisions.